Penggunaan Media Berbasis Android Dalam Pembelajaran dan Penyelesaian Solusi Soal Kalkulus - Sucipto, Lalu; Syaharuddin, Syaharuddin (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2024)
This research aims to evaluate the effectiveness of using Android-based media in calculus learning and problem-solving, considering the differences based on the students' school backgrounds (religious and general). The study involved 83 students, with 45 from religious school backgrounds and 38 from general school backgrounds. The research instrument utilized a Likert Scale questionnaire comprising 13 items, designed to measure students' perceptions and experiences regarding the effectiveness of Android-based media in calculus learning. The data analysis technique employed the t-test. The statistical results revealed a t-test value of 0.006, with a significance level (Sig.) of 0.995. These findings indicate a significant difference in the effectiveness of using Android-based media between students from religious and general school backgrounds in the context of calculus learning. These results contribute to understanding the impact of Android-based media on calculus learning outcomes, particularly considering students' diverse school backgrounds. The practical implications of this research can serve as a guide for designing more effective learning strategies, especially in harnessing Android-based technology within educational environments.